Mechanisms of damage and therapies for cardiac amyloidosis: a role for inflammation? - Bellofatto, Ilaria Anna; Nikolaou, Panagiota Efstathia; Andreadou, Ioanna; Canepa, Marco; Carbone, Federico; Ghigo, Alessandra; Heusch, Gerd; Kleinbongard, Petra; Maack, Christoph; Podesser, Bruno K.; Stamatelopoulos, Kimon; Stellos, Konstantinos; et al. (Clinical research in cardiology, 2024)
The term cardiac amyloidosis (CA) refers to the accumulation of extracellular amyloid deposits in the heart because of different conditions often affecting multiple organs including brain, kidney and liver. Notably, cardiac involvement significantly impacts prognosis of amyloidosis, with cardiac biomarkers playing a pivotal role in prognostic stratification. Therapeutic management poses a challenge due to limited response to conventional heart failure therapies, necessitating targeted approaches aimed at preventing, halting or reversing amyloid deposition. Mechanisms underlying organ damage in CA are multifactorial, involving proteotoxicity, oxidative stress, and mechanical interference. While the role of inflammation in CA remains incompletely understood, emerging evidence suggests its potential contribution to disease progression as well as its utility as a therapeutic target. This review reports on the cardiac involvement in systemic amyloidosis, its prognostic role and how to assess it. Current and emerging therapies will be critically discussed underscoring the need for further efforts aiming at elucidating CA pathophysiology. The emerging evidence suggesting the contribution of inflammation to disease progression and its prognostic role will also be reviewed possibly offering insights into novel therapeutic avenues for CA.